Nonhematologic and Hematologic Factors in Spontaneous Intracerebral Hemorrhage - Kwaan, Hau C. (Seminars in Thrombosis and Hemostasis, 2021)
Spontaneous intracerebral hemorrhage is defined as nontraumatic bleeding into the brain without vascular malformations or presence of tumor. It occurs in about a third of all strokes and has a high mortality and morbidity. Risk factors that determine the outcome are incompletely understood. Known factors include older age, male gender, Asian ethnicity, hypertension, and comorbidity such as inherited or acquired bleeding diathesis and use of antithrombotic drugs. Likewise, the clinical characteristics of the hematoma such as location and volume of the hematoma and other imaging features are also important. Hematoma extension or expansion is a complication with an unfavorable outcome. Recognition of risk factors for hematoma expansion and measures to prevent it, such as blood pressure lowering, will improve the outcome. Enhanced diagnostic methods, especially in imaging techniques developed over the past decade, have not only led to a better understanding of the pathophysiology of spontaneous intracerebral hemorrhage but also of the factors that influence hematoma expansion. An improved knowledge is essential to better management, minimizing hematoma expansion and leading to a healthier outcome.
Keywords: intracerebral hemorrhage; hematoma expansion; hypertension; biomarkers; platelet function